2016
DOI: 10.18632/oncotarget.7561
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA dysregulation and esophageal cancer development depend on the extent of zinc dietary deficiency

Abstract: Zinc deficiency (ZD) increases the risk of esophageal squamous cell carcinoma (ESCC), and marginal ZD is prevalent in humans. In rats, marked-ZD (3 mg Zn/kg diet) induces a proliferative esophagus with a 5-microRNA signature (miR-31, -223, -21, -146b, -146a) and promotes ESCC. Here we report that moderate and mild-ZD (6 and 12 mg Zn/kg diet) also induced esophageal hyperplasia, albeit less pronounced than induced by marked-ZD, with a 2-microRNA signature (miR-31, -146a). On exposure to an environmental carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 81 publications
(141 reference statements)
3
53
0
Order By: Relevance
“…Lastly, a number of non‐protein molecules (hormones and indoles) were demonstrated to regulate miR‐31 expression (Kuokkanen et al, ; Busbee et al, ). A number of studies reported that miR‐31 expression is activated by RELA (p65 subunit of NF‐κB) and SP1 (a zinc‐finger transcription factor) in esophageal cells under conditions that lack zinc (Alder et al, ; Fong et al, ; Taccioli et al, ). These data were correlative, and no molecular mechanism has been elucidated.…”
Section: Regulation Of Mir‐31 Expressionmentioning
confidence: 99%
“…Lastly, a number of non‐protein molecules (hormones and indoles) were demonstrated to regulate miR‐31 expression (Kuokkanen et al, ; Busbee et al, ). A number of studies reported that miR‐31 expression is activated by RELA (p65 subunit of NF‐κB) and SP1 (a zinc‐finger transcription factor) in esophageal cells under conditions that lack zinc (Alder et al, ; Fong et al, ; Taccioli et al, ). These data were correlative, and no molecular mechanism has been elucidated.…”
Section: Regulation Of Mir‐31 Expressionmentioning
confidence: 99%
“…19 Fong et al found that EC incidence is highest in severely Zn deficient rats and that severe Zn deficiency alone induced a highly proliferative/inflammatory esophagus accompanied with oncogenic 5-miRNA signatures (miR-31, miR-223, miR-21, miR-146b and miR-146a; up 3.7-to 4.9fold) ( Table 1). 20,21 Wen et al investigated the expression of miR-21 in 76 pairs of human EC tissues and adjacent para-cancerous tissues and the EC cell line, TE-13. MiR-21 expression was significantly increased in EC tissues and EC TE-13 cells.…”
Section: Zn Deficiency Affects the Development Of Ec By Regulating MImentioning
confidence: 99%
“…31 Upregulation of oncogenic miR-223, miR-31, and miR-21 is accompanied by downregulation of their tumor suppressor targets in EC Fong et al demonstrated that Zn deficiency upregulated miR-21, miR-31, and miR-223 expression, which was accompanied by downregulation of their tumor suppressor targets, PDCD4, serine/threonine kinase 40 (STK40), and Fbox and WD repeat domain-containing 7 (FBXW7) in a Zn deficient rat EC model. 20 The FBXW7 gene locus, which is located at chromosome 4q32, is frequently decreased in a variety of human tumors. FBXW7 coordinates the ubiquitin-dependent proteolysis of several critical cellular regulators, thereby controlling essential biological processes, including cell cycle, differentiation, and apoptosis.…”
Section: Zn Deficiency Affects the Development Of Ec By Regulating MImentioning
confidence: 99%
See 2 more Smart Citations